17O NMR spectroscopy of crystalline microporous materials. Issue 14 (17th March 2021) - Ashbrook, Sharon E.; Davis, Zachary H.; Morris, Russell E.; Rice, Cameron M.
Abstract : Cost-effective and atom-efficient isotopic enrichment enables 17 O NMR spectroscopy of microporous materials to be used to probe local structure and disorder and to explore chemical reactivity. Abstract : Microporous materials, containing pores and channels of similar dimensions to small molecules have a range of applications in catalysis, gas storage and separation and in drug delivery. Their complex structure, often containing different types and levels of positional, compositional and temporal disorder, makes structural characterisation challenging, with information on both long-range order and the local environment required to understand the structure–property relationships and improve the future design of functional materials. In principle, 17 O NMR spectroscopy should offer an ideal tool, with oxygen atoms lining the pores of many zeolites and phosphate frameworks, playing a vital role in host–guest chemistry and reactivity, and linking the organic and inorganic components of metal–organic frameworks (MOFs). However, routine study is challenging, primarily as a result of the low natural abundance of this isotope (0.037%), exacerbated by the presence of the quadrupolar interaction that broadens the spectral lines and hinders the extraction of information. In this Perspective, we will highlight the current state-of-the-art for 17 O NMR of microporous materials, focusing in particular on cost-effective and atom-efficient approaches to enrichment, the use of enrichment to explore chemical reactivity, the challenge of spectral interpretation and the approaches used to help this and the information that can be obtained from NMR spectra. Finally, we will turn to the remaining challenges, including further improving sensitivity, the high-throughput generation of multiple structural models for computational study and the possibility of in situ and in operando measurements, and give a personal perspective on how these required improvements can be used to help solve important problems in microporous materials chemistry.